2008
DOI: 10.1158/1078-0432.ccr-07-4741
|View full text |Cite
|
Sign up to set email alerts
|

Class III β-Tubulin Isotype Predicts Response in Advanced Breast Cancer Patients Randomly Treated Either with Single-Agent Doxorubicin or Docetaxel

Abstract: Purpose: To evaluate the role of microtubule-associated variables as potential predictors of response and clinical outcome in patients with advanced breast cancer receiving single-agent docetaxel or doxorubicin chemotherapy. Experimental Design: The analysis was done on 173 tumor samples from patients with locally advanced or metastatic breast cancer who have participated in theTAX-303 phase III trial in which patients were randomly assigned to receive docetaxel or doxorubicin. Expression of total a-and h-tubu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 40 publications
6
34
1
Order By: Relevance
“…Several clinical studies have shown that high levels of βIII-tubulin expression in tumor cells are associated with low response rates and poorer survival in patients treated with taxane-based chemotherapies (13)(14)(15)(16)(17)39). Our findings in PCa were consistent with the previous studies and highlight that the expression of βIII-tubulin is associated with non-organ-confined disease, metastatic lymph nodes, and PSA failure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several clinical studies have shown that high levels of βIII-tubulin expression in tumor cells are associated with low response rates and poorer survival in patients treated with taxane-based chemotherapies (13)(14)(15)(16)(17)39). Our findings in PCa were consistent with the previous studies and highlight that the expression of βIII-tubulin is associated with non-organ-confined disease, metastatic lymph nodes, and PSA failure.…”
Section: Discussionsupporting
confidence: 91%
“…A growing body of preclinical and clinical data now suggests that increased expression of one particular β-tubulin isoform, class III β-tubulin (βIII-tubulin), confers cancer cell resistance to taxanes (9)(10)(11) and that βIII-tubulin resistance to taxanes is clinically relevant for human lung, breast, and ovarian cancers (12). For these human malignancies, high tumor cell expression of βIII-tubulin was associated with significantly poorer survival rates in patients treated with taxane-based chemotherapy (13)(14)(15)(16)(17). For lung cancer, one study suggested that tumor cell βIII-tubulin expression was a prognostic factor for men who did not receive adjuvant chemotherapy (18).…”
Section: Introductionmentioning
confidence: 99%
“…Tubulin III isotype has been repeatedly reported to correlate with response and outcome in patients receiving taxanebased regimens for lung cancer or ovarian cancer (31,32). We recently reported that docetaxel was more active than doxorubicin in women with metastatic breast cancers with a high level of tubulin III isotype (33). The level of expression of glu tubulin, a posttranslationally modified form of α tubulin correlated with microtubule stability, has previously been reported to be correlated with tumor aggressiveness in breast cancer patients (34).…”
Section: Discussionmentioning
confidence: 93%
“…As in the case of doxorubicin, most published studies contain significant weaknesses (retrospective and unplanned nature, and small sample size) and therefore, the real predictive values of HER2 [56,57], microtubule associated parameters [58][59][60], and ki-activity, while the remaining markers (PR, HER2, TOP2A gene alterations or topo2a protein expression, tau protein, p27, Ki67) were not.…”
Section: Discussionmentioning
confidence: 99%